Reply to Comment on 'Development of a primary standard for absorbed dose from unsealed radionuclide solutions'. (27th July 2017) - Billas, I; Shipley, D; Galer, S; Bass, G; Sander, T; Fenwick, A; Duane, S; Smyth, V
Abstract: This article is a reply to the comment from Ross (2017 Metrologia 54 610) on our paper (Billas et al 2016 Metrologia 53 1259) 'Development of a primary standard for absorbed dose from unsealed radionuclide solutions'.